Perancangan Pengendalian Internal Penerimaan Dan Pengeluaran Kas Berbasis Coso Integrated Framework Pada RA Qurani Islamic Centre Wasilah Subuh Jakarta - Risma Apriyani; Hafifah Nasution; Marsellisa Nindito (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Internal control is an important element in ensuring accountability and transparency in financial management, especially in foundation based educational institutions that manage funds from various sources. Cash, as the most liquid asset, has the highest risk of misuse if it is not supported by an adequate internal control system. Various cases of fund misappropriation in educational foundations show that weak internal control structures, can open up opportunities for fraud. This study aims to analyze the condition of internal control over cash receipts and disbursements and to design an internal control system based on the COSO integrated framework at RA Qurani Islamic Center Wasilah Subuh Jakarta.  The research method used is a qualitative method with a descriptive approach. This research was conducted at RA Qurani Islamic Center Wasilah Subuh Jakarta with data collection techniques in the form of interviews, observations, and document analysis. The development of internal control design was carried out using the System Development Life Cycle (SDLC) approach with a Waterfall model limited to the planning, analysis, and design. The results indicate that internal control over cash receipts and disbursements at RA Qurani Islamic Centre is not yet fully effective based on the COSO Integrated Framework, particularly in the control environment, control activities, and monitoring components. These weaknesses are reflected in inadequate separation of duties, the absence of written standard operating procedures (SOPs), and the use of non-standardised supporting documents. As a follow-up, this study develops a COSO-based internal control design for cash management, including improvements in organisational structure, clarification of roles and responsibilities, development of SOPs and workflows, and standardisation of cash documents and reports. This design is expected to enhance internal control effectiveness, accountability, and transparency in cash management.